2020
DOI: 10.3389/fmicb.2020.01541
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Disturbance Stimulated Nitrification and Altered Ammonia Oxidizer Community Structure in Lake Okeechobee and St. Lucie Estuary (Florida)

Abstract: Nitrification is an important biological link between oxidized and reduced forms of nitrogen (N). The efficiency of nitrification plays a key role in mitigating excess N in eutrophic systems, including those with cyanobacterial harmful algal blooms (cyanoHABs), since it can be closely coupled with denitrification and removal of excess N. Recent work suggests that competition for ammonium (NH 4 +) between ammonia oxidizers and cyanoHABs can help determine microbial community structure. Nitrification rates and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 118 publications
(218 reference statements)
0
13
0
Order By: Relevance
“…Additionally, seasonal algal blooms may be an important factor that could affect the temporal patterns of ammonia‐oxidising microbial communities. Some researchers suggested that ammonia‐oxidising microorganisms compete with algae and other primary producers for NH 4 + (Glibert et al., 2016; Hampel et al., 2018, 2020). In the present study, the results of water quality analysis showed that the increases in the concentrations of Chl a in the April–August months were related to the decreases in the concentrations of DIN, NH 4 + , NO3, and PO43 in the relevant months, suggesting that summer algal blooms were possibly responsible for contributing to the decrease of ambient nutrient concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, seasonal algal blooms may be an important factor that could affect the temporal patterns of ammonia‐oxidising microbial communities. Some researchers suggested that ammonia‐oxidising microorganisms compete with algae and other primary producers for NH 4 + (Glibert et al., 2016; Hampel et al., 2018, 2020). In the present study, the results of water quality analysis showed that the increases in the concentrations of Chl a in the April–August months were related to the decreases in the concentrations of DIN, NH 4 + , NO3, and PO43 in the relevant months, suggesting that summer algal blooms were possibly responsible for contributing to the decrease of ambient nutrient concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As pH declined, higher concentrations of NO 3 were observed (up to 2 lM) during the drought and in the years following the storm events, in all cases being highest at the end of the dry season or early wet season. Similarly, Hampel et al (2020) observed increases in nitrification in Lake Okeechobee and St Lucie Estuary, Florida, following Hurricane Irma. Thus, if nitrification is inhibited by temperature of pH, any available NH 4…”
Section: Picocyanobacterial Blooms: Ammonium and Nitratementioning
confidence: 69%
“…Levels of TN, microcystin, and toxic Microcystis strains are highly and significantly correlated across the lake and estuary gradient. In addition, the competition between cyanobacteria and nitrifiers for ammonium impacts the capacity for denitrification in the system [32,33].…”
Section: Spatial Variability Of Physicochemical Variablesmentioning
confidence: 99%
“…Qian et al (2007) [30] assessed long-term data (1979 to 2004) of water quality constituents in major canals and found that almost all nutrient species had significantly higher concentrations in the wet than in the dry season. Studies by Hampel et al (2020) [32], Kramer et al (2018) [33], and Oehrle et al (2017) [35] demonstrated the key role of nitrogen species and salinity in toxic Microcystis blooms in the lake-estuary continuum. The South Florida Water Management District (SFWMD) and the Florida Department of Environmental Protection (FDEP) continuously assess the water quality of the estuary and the lake.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation